Evidence Gaps in Clinical Trials of Pharmacologic Treatment for H1-Antihistamine-Refractory Chronic Spontaneous Urticaria: A Systematic Review and Future Perspectives - Surapon Nochaiwong; Mati Chuamanochan; Chidchanok Ruengorn; Kednapa Thavorn (MDPI AG, 2022)
No data addressing issues concerning disparities in participant and trial characteristics and trial outcome reporting have been established in clinical trials for H1-antihistamine-refractory chronic spontaneous urticaria (CSU). To better harmonize and compare the different treatment interventions, we systematically evaluated the overall landscape of pharmacological treatments for H1-antihistamine-refractory CSU clinical trials published between 2000 and 2021. This systematic review included 23 randomized clinical trials involving 2480 participants from 22 countries. We found significant increases in the number of globally published and newly tested drugs, especially biologic drugs. Regarding relatively small trials, we found that people living with H1-antihistamine-refractory CSU who were identified as members of minority groups (non-white population), populations of regions other than North America/Europe, and populations of low- to lower/upper-middle-income countries are underrepresented. Most trials were designed to evaluate treatment efficacy and safety profiles; however, less than half of the included trials reported the patient's perspective in terms of patient-reported outcomes. Disparities in outcome reporting, including clinimetric tools for assessing treatment response and outcome sets, were observed. To close the evidence gap in H1-antihistamine-refractory CSU trials, strategies for improving trial and participant enrollment and standardizing core outcome sets for trial reporting are needed.